(untitled) (Research, Society and Development, 2022)
Introduction: HIV infection has the potential to generate several damages to the human body, among them hearing loss has gained increasing attention and generating several studies. The hypotheses about the association of HIV/AIDS and hearing loss in the scientific literature include: the very action of the virus in the inner ear and central nervous system, opportunistic infections and their potentially ototoxic treatments and antiretroviral therapy (ART). Objective: To describe the scientific findings related to the causes of hearing loss in HIV-infected individuals in the last 15 years. Methodology: This article is an integrative review of the literature in the electronic databases PUBMED and LILACS, using combinations of the following descriptors: "Hearing loss", "HIV" (HIV), "Deafness”) and "Antiretroviral Therapy". We found 71 articles published between 2006 and 2021, in English and Portuguese, of which only 11 met the proposed criteria and were included in the review, plus 3 articles selected by manual search due to their relevance and recent publication. Results: After analyzing the studies, relevant factors that influence hearing loss in HIV-infected patients emerged: age and viral/CD4 load, and sensorineural loss was the most common type. Conclusion: It can be concluded that the causes of hearing loss in individuals with HIV are multifactorial, since no statistically significant association was found between antiretroviral therapy, opportunistic diseases and viral exposure with hearing loss in patients with HIV/AIDS.